Implementasi Media Complete the Sentence terhadap Kemampuan Membaca dan Motivasi Belajar Kelas 3 SDN 16 Bireuen: The Implementation of Complete the Sentence Media on Reading Ability and Learning Motivation of Grade 3 Students at SDN 16 Bireuen - Supiati Supiati; Alfi Syahrin; Yulia Santi (Edu Cendikia: Jurnal Ilmiah Kependidikan, 2026)
Reading proficiency is a crucial foundation for literacy among elementary school students. However, some students in lower grades still struggle to comprehend simple texts due to limited reading skills and low learning motivation. The "Complete the Sentence" instructional medium offers an alternative approach that actively engages students in reading comprehension. This study employed a quantitative approach using a quasi-experimental, non-equivalent control group design. The sample consisted of 30 students in the experimental group and 23 students in the control group at UPTD SDN 16 Bireuen. Reading proficiency data were collected via an 18-item multiple-choice test, while learning motivation was measured using a 15-statement, four-point Likert scale questionnaire. Data analysis involved the Paired Samples t-Test, Mann-Whitney U test, One-Sample t-Test, and Multivariate Analysis of Variance (MANOVA). The results indicate that the "Complete the Sentence" medium had a significant impact on students' reading proficiency, evidenced by an increase in the mean score from 57.83 to 83.50 and an N-Gain score of 0.60 (moderate-to-high category). Student learning motivation also improved, reaching an average of 79.9% (high category). MANOVA results showed a Wilks' Lambda value of 0.247 and an ?² of 0.753. The "Complete the Sentence" medium effectively enhanced both reading proficiency and learning motivation among third-grade students at UPTD SDN 16 Bireuen—both individually and simultaneously—making it a viable instructional alternative to support literacy and motivation in elementary education.